Anagyrus Howard (Hymenoptera: Encyrtidae) parasitoids of the invasive Delottococcus aberiae (De Lotto) (Hemiptera: Pseudococcidae) from South Africa, with description of two new species - Guerrieri, Emilio; Cascone, Pasquale (Zootaxa, 2018)
Delottococcus aberiae is an invasive mealybug native to South Africa that has been accidentally introduced into Spain. A survey of natural enemies in its native area to potentially be used for biological control of this pest resulted in a number of species, among which four belonged to the genus Anagyrus. Following an integrative approach using morphological and molecular data, two species new to science are here described and compared with closely related ones: Anagyrus aberiae sp.n. and Anagyrus antoniae sp.n. A dichotomous key to separate the species of Anagyrus attacking D. aberiae in South Africa is provided. [Zoobank LSID: Anagyrus aberiae Guerrieri sp. nov. (Fig. 1–7): LSID urn:lsid:zoobank.org:pub:8CF8983B-93DC-4ECF-A8FB-CF76E94319B3 Anagyrus antoniae Guerrieri sp. nov. (Fig. 8–12): LSID urn:lsid:zoobank.org:pub:8CF8983B-93DC-4ECF-A8FB-CF76E94319B3]